Re-thinking human capital acquisition for entrepreneurship: A holistic multidimensional approach - Crespo, N.; Simões, N.; Dosumu, O. (International Journal of Education Economics and Development, 2024)
Given the substantial interest around the study of entrepreneurship, understanding the intricate network of factors that explain the decisions about human capital is of critical importance. Decisions concerning knowledge, skills and abilities are multidimensional since there are many modes, categories, and components of human capital acquisition. Human capital may come from a set of choices or a set of processes. The choices and processes are disaggregated into four categories: (i) what human capital entrepreneurs choose to acquire; (ii) where they want to acquire such human capital; (iii) how they want to acquire the human capital; (iv) when they want to acquire human capital. Furthermore, it is also important to understand the drivers/motivations of entrepreneurs regarding human capital acquisition. This paper is an in-depth organization and review of the existing literature. We present a roadmap connecting the points that remain disperse and fragmented. In addition, suggestions for future research are provided.